A new generation of Aerated Filter - Martin, J. (Cranfield University, School of Water Sciences, 1999)
The use of the activated sludge process is a very well known technology. It is and has been used very widely in full scale plants from its first development at the Davyhulme works in Manchester. However this process becomes very difficult to upgrade or to extend in order to ensure compliance with either more stringent discharge consent conditions or to achieve the same quality of discharge where increasing flows are the problem. This problem of upgrading or extension to existing works led OTV almost twenty years ago to develop the bio-filter process. This process consists of essentially biological filters operating either in the down flow or up flow mode, the main benefits of this system being they are compact in their space requirements, together with their ability to combine both filtration and aerobic/anaerobic bio degradation. They are used for the removal of suspended solids, COD, BOD, ammonia (and nitrate) either in the secondary or the tertiary treatment stage, plus with the use of a precipitating chemical, they can also be used for the removal of phosphates.